Effect of ultimate pH on quality of aged Longissimus dorsi muscle of Zebu Nellore (Bos indicus) during long-term frozen storage - Coaguila Gonza, Milagros Maribel (2023)
Despite the relatively high occurrence of bovine meat with intermediate to high ultimate pH (pHu), there is a lack of studies focused on the effects of long-term conventional air-blasting freezing storage on quality parameters of commercial beefs of Zebu Nellore (Bos indicus) with varying pHu ranges. The objective of this work was to evaluate the influence of pHu ranges [normal (≤5.79), intermediate (5.80 to 6.19), and high (≥6.20)] and long-term frozen storage on quality parameters of aged Longissimus dorsi beefs of Zebu Nellore (Bos indicus). The aging conditions were set at 2 °C for 14 days, while the freezing conditions were set at − 20 °C, and samples were collected after 3, 6, 9, and 12 months of storage. The results indicated that the pHu influenced meat quality parameters, as well as the chemical forms of myoglobin, which changed throughout the frozen storage, leading to a brighter red color, especially for the normal pHu beef samples, likely due to increased oxymyoglobin content. Frozen storage improved tenderness, with high pHu beef samples being the more tender after 12 months, potentially due to lower protein oxidation, as measured by the carbonyl content. Increased drip loss was observed over freezing time, with a concomitant decrease in protein solubility, especially for myofibrillar and sarcoplasmic proteins, which differed among the pHu ranges. These findings are valuable for determining freezing time as a preservation strategy to maintain beef quality within different pHu ranges. © 2023 Elsevier Ltd